Altered mental status: what is the diagnosis?. (12th February 2015) - Gupta, Arjun; Shelton, William; Singh, Rajeev; Pandey, Ambarish
Abstract : We report a patient presenting with a 2-day history of altered mental status and lethargy. She had recently started taking prednisone for suspected 'autoimmune arthritis'. Clinical deterioration in hospital characterised by increasing confusion, alternating hyperarousal and somnolence, auditory hallucinations and eventual unresponsiveness led to an intensive care unit transfer. Initial laboratory and radiological testing did not reveal a cause for her symptoms. The only abnormality detected was antithyroid peroxidase antibody levels elevated to >900 IU/mL with patient demonstrating marked clinical improvement within 24 h of receiving high-dose steroids and plasmapheresis. Hashimoto's encephalitis is an underdiagnosed reversible neuropsychiatric disorder with unknown pathogenesis. Recent studies indicate that autoimmune encephalopathy and specifically Hashimoto's encephalitis is under-reported. Our case demonstrates the importance of maintaining a wide differential for altered mental status, especially after negative initial diagnostic work-up of more common aetiologies. Although steroids are an effective treatment for Hashimoto's encephalitis, the addition of early plasmapheresis may be indicated in patients with severe presentation and those who develop disease while taking steroids.